Structural basis for activation of fluorogenic dyes by an RNA aptamer lacking a G-quadruplex motif. Issue 1 (December 2018) - Shelke, Sandip; Shao, Yaming; Laski, Artur; Koirala, Deepak; Weissman, Benjamin; Fuller, James; Tan, Xiaohong; Constantin, Tudor; Waggoner, Alan; Bruchez, Marcel; Armitage, Bruce; Piccirilli, Joseph
Abstract The DIR2s RNA aptamer, a second-generation, in-vitro selected binder to dimethylindole red (DIR), activates the fluorescence of cyanine dyes, DIR and oxazole thiazole blue (OTB), allowing detection of two well-resolved emission colors. Using Fab BL3-6 and its cognate hairpin as a crystallization module, we solved the crystal structures of both the apo and OTB-SO3 bound forms of DIR2s at 2.0 Å and 1.8 Å resolution, respectively. DIR2s adopts a compact, tuning fork-like architecture comprised of a helix and two short stem-loops oriented in parallel to create the ligand binding site through tertiary interactions. The OTB-SO3 fluorophore binds in a planar conformation to a claw-like structure formed by a purine base-triple, which provides a stacking platform for OTB-SO3, and an unpaired nucleotide, which partially caps the binding site from the top. The absence of a G-quartet or base tetrad makes the DIR2s aptamer unique among fluorogenic RNAs with known 3D structure. The DIR2s RNA aptamer activates the fluorescence of cyanine dyes allowing detection of two well-resolved emission colors. Here authors solve the crystal structures of the apo and OTB-SO3 fluorophore-bound DIR2s and show how the fluorophore ligand is bound.